2017
DOI: 10.1177/0269881117732514
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant efficacy of subanesthetic-dose ketamine does not correlate with baseline subcortical volumes in a replication sample with major depressive disorder

Abstract: Background This study sought to reproduce, in a larger sample, previous findings of a correlation between smaller raw 3-Tesla (3T) hippocampal volumes and improved antidepressant efficacy of ketamine in individuals with major depressive disorder (MDD). A secondary analysis stratified subjects according to functional BDNF rs6265 (val66met) genotype. Methods Unmedicated subjects with treatment-resistant MDD (n=55) underwent baseline structural 3T MRI. Data processing was conducted with FSL/FIRST and Freesurfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
1
9
1
1
Order By: Relevance
“…In the exploratory analysis in our sample, baseline volumes of the right thalamus and left Sub head in the hippocampus were positively correlated with changes in MADRS scores, such that patients with relatively larger right thalamus and left Sub head volumes had greater improvements in depressive symptoms following six doses of ketamine. These findings disagreed with the findings of previous studies that showed that patients with smaller pretreatment hippocampal volumes were more likely to achieve better clinical improvements and that smaller left and right thalamic volumes were correlated with the antidepressant response to ketamine in BDNF 66Met allele carriers 18,22 . However, the present findings were in line with those of our previous study that showed that patients with better neurocognitive function, an index that could reflect hippocampal function, may be more likely to benefit from ketamine treatment 24 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the exploratory analysis in our sample, baseline volumes of the right thalamus and left Sub head in the hippocampus were positively correlated with changes in MADRS scores, such that patients with relatively larger right thalamus and left Sub head volumes had greater improvements in depressive symptoms following six doses of ketamine. These findings disagreed with the findings of previous studies that showed that patients with smaller pretreatment hippocampal volumes were more likely to achieve better clinical improvements and that smaller left and right thalamic volumes were correlated with the antidepressant response to ketamine in BDNF 66Met allele carriers 18,22 . However, the present findings were in line with those of our previous study that showed that patients with better neurocognitive function, an index that could reflect hippocampal function, may be more likely to benefit from ketamine treatment 24 .…”
Section: Discussioncontrasting
confidence: 99%
“…Abdallah et al 18 tested the pretreatment hippocampal volume in 13 MDD patients who received a single infusion of ketamine and found a smaller left hippocampus volume was correlated with a greater symptom improvement 24 h after the infusion 18 . Niciu and colleagues reported that baseline subcortical volumes were not related to the antidepressant response in 55 unmedicated patients with treatment-resistant depression (TRD) within 24 h of a single infusion of ketamine 22 . However, combined with the brain-derived neurotrophic factor (BDNF) genotype, baseline bilateral thalamic volume was positively correlated with ketamine's antidepressant response in met carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, preliminary data on the role of fast‐acting antidepressants on mediating changes in the volume of the DG support the idea that antidepressant treatment does not restore the lost volume. A recent study did not identify a correlation between hippocampal volume changes and clinical efficacy of ketamine (Niciu et al, 2017).…”
Section: Structural and Molecular Changes In The Dg In Depressionmentioning
confidence: 96%
“…127 These data suggest that a deeper investigation in the regulatory mechanisms of glutamate/GABA balance is of interest, 123,126 and adenosine-dopamine signaling might play an important role, 125 especially considering the glutamate-GABA modulatory effect of both A 2A and D 2 receptors individually. 128,129 The aforementioned findings regarding the A 2A receptor and the D 2 receptor in GABAergic neurons were the first evidence of a possible role of adenosine-dopamine receptors integrated functional control of neuropsychiatric symptoms; however, there is emerging evidence of other heteromers' participation. As the role of the D 3 receptor in mood disorders is being investigated, 69,78,130 the antagonistic modulation of A 2A -D 3 heteromer is proposed as a possible antischizophrenic approach.…”
Section: Dopaminergic System and Moodmentioning
confidence: 99%